Development of the model and method of selecting the description of rational architecture of information system - Евланов, Максим Викторович (Eastern-European Journal of Enterprise Technologies, 2016)
The results of research of the model and method of selecting the description option of the rational architecture of the developed information system are considered. The method of synthesis of description options of the architecture of the developed IS based on the CLOPE algorithm is proposed. The following is developed: a) formal descriptions of the functions of the Provider’s and the Customer’s objectives that maximize the degree of satisfaction of their functional requirements to IS; b) the game-theoretic model of selecting the option of description of the rational architecture of the developed information system, which is a bimatrix noncooperative game of the IT service Provider and Customer; c) the method of finding a solution to the game of the Provider and the Customer to select the option of description of the rational architecture of the developed information system based on pure strategies by finding the Nash equilibrium point, which is a sequence of actions aimed at finding the option of description of the architecture of the developed IS, which to the greatest extent meets the Provider’s and the Customer’s requirements. The proposed solutions allow considering the process of designing the architecture of the developed IS as the decision-making problem of selecting the rational option of description of the architecture of the given system. The initial data for solving this problem are formal descriptions of the knowledge obtained from the descriptions of the system requirements. In the course of solving this problem, it is proposed to synthesize a set of descriptions of the architecture of the developed IS on the basis of formal descriptions of knowledge about individual requirements. Then, it is suggested to select an option in the set that to the greatest extent meets the expectations of the Provider and the Customer of the developed system. This approach to designing the architecture of the developed IS is unique in current research and existing requirements management systems. The formal descriptions of the functions of the Provider’s and the Customer’s objectives, game-theoretic model and method allow automating the process of designing the architecture of the developed information system. This is achieved through the development of formal models and methods, describing the operations of forming the representations of IS requirements on the knowledge level, synthesis of a set of the architecture description options on the basis of the generated representations of requirements and selection of the description option of the rational architecture of the developed IS. These methods allow transition from the synthesis of descriptions of the information system as a plurality of individual functional requirements to the synthesis of a unified description of the information system, taking into account the overlapping of individual functional requirements. This will improve the system-wide effect of the developed system through harmonizing the descriptions of individual functions of this system in the early stages of its life cycle. The developed model and method, as well as information system development tools on their basis, allow unifying and simplifying the processes of pre-project survey and design of information systems. This, in turn, reduces the time and cost to implement IT projects of development and upgrading of information systems. In addition, the use of the developed methods allows adapting the Provider’s previous solutions to the peculiarities of the Customer’s new requirements.